Importancia de las zonas francas exclusivas de servicios en el Valle del Cauca (2022)
The concession of a Free Trade Zone increases the possibility that several businessmen, entrepreneurs or already experienced in the market, can expand their portfolio of services and / or products internationally, which positions any country as an exporter of goods and services that can boost its economy. Currently, we can observe an exponential growth in companies that offer services to other companies abroad and ZONAMERICA being the only Free Trade Zone of services has announced the construction of its second building with aspirations for the approval of the third building, thus approaching the final goal of 14 buildings. Therefore, this research promotes the expansion of Free Trade Zones, especially those of services that can enhance the development of a country like Colombia, where services are an important part of the GDP and the economy of the national territory. A Free Trade Zone of services will expand the opportunities for small and medium entrepreneurs who are starting up and can project international sales.